SPESIFIKASI TES DIAGNOSTIK EJAAN DAN TANDA BACA BERBASIS HIGH ORDER THINKING SKILLS - Pratiwi, Mega; Fitriani, Yustina (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
The ability of students to apply correct spelling and punctuation remains relatively low, which may negatively impact the quality of critical thinking in academic writing. Therefore, a diagnostic test instrument is needed not only to assess their skills but also to promote higher-order thinking skills (HOTS) in order to strengthen their understanding and application of language rules more deeply. The aim of this study is to develop a guideline for the construction of a diagnostic test on spelling and punctuation based on HOTS. The method used is a six-stage literature study, consisting of: (1) problem identification, (2) literature search, (3) literature selection, (4) literature organization, (5) synthesis and critical analysis, and (6) writing the literature review results. The results of this study include: (1) the development of a diagnostic test on spelling, (2) the development of a diagnostic test on punctuation, (3) scoring techniques, and (4) feedback mechanisms. The scientific contributions of this research are: (1) a systematic development of diagnostic test specifications for spelling and punctuation, with an emphasis on the cognitive levels of HOTS (C4-analysis, C5-evaluation, C6-creation), (2) the direct integration of the Indonesian Spelling Guidelines with HOTS indicators, making the test not only normative but also reflective and productive, and (3) the combination of multiple-choice and open-ended (C6) question formats in one diagnostic system — in accordance with the principles of multiformat assessment.